IDENTIFIKASI STRUKTUR GEOLOGI DAN PENGARUHNYA TERHADAP SUHU PERMUKAAN TANAH BERDASARKAN DATA LANDSAT 8 DI LAPANGAN PANASBUMI BLAWAN - Azhari, Anjar Pranggawan; Maryanto, Sukir; Rachmansyah, Arief (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2016)
This paper presents the use of remote sensing methods for identifying geological structures on the Blawan-Ijen geothermal field and its system. Remote sensing data, specifically Landsat 8 and DEM SRTM, were utilized to extract lineaments from the 753 multispectral band and derive land surface temperature (LST) from a single thermal infrared band using a retrieval method. Surface emissivity was determined based on the Normalized Difference Vegetation Index (NDVI) of the study area. Remote sensing analysis proved to be an effective approach for identifying geological structures from the surface that control thermal manifestations in the Blawan geothermal field. The results indicate that the Blawan fault is the primary structure in the geothermal field, associated with high LST and hot springs. Interpretation suggests that the reservoir of the Blawan-Ijen geothermal system extends from Plalangan to the southwest area.